Financial Performance and Stock Price: Another Review on Banks Listed in Indonesia Stock Exchange - Erlyta Agustine Noviyanti; Caecilia Wahyu Estining Rahayu; Christina Heti Tri Rahmawati (Soegijapranata Catholic University, 2021)
Financial performance is an important factor to attract investors in buying stocks. This study aims to determine the influence of financial performance measured by Non-Performing Loan Ratio (NPL), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Net Profit Margin (NPM) on price of stocks of banks listed in the Indonesia Stock Exchange (IDX) during 2014-2018. Of 43 banks, there were only 31 banks fit the criteria under purposive sampling technique. The data used in this study are secondary data obtained from the official website of Indonesia Stock Exchange (www.idx.co.id). Multiple linear regression analysis was applied for analyzing the data that were tested for classic assumptions. The results showed that simultaneously NPL, LDR, CAR, DER, ROA and NPM had significant influence on stock prices. Partially, the result showed that only ROA and NPM had a significant influence on stock prices. Banks must then focus mainly on ROA and NPM in attracting investors.